THE PLACE AND ROLE OF ARTIFICIAL INTELLIGENCE CHATBOTS IN ADULT EDUCATION AND TRAINING OF ADULT EDUCATORS : Received: 25th August 2021; Revised: 3rd December 2021, 30th December 2021, 29th March 2022; Accepted: 1st April 2022 - Igbafe, Eucharia Chinwe (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Artificial intelligence chatbots are becoming the new trend of technology in the education sector and competitively changing teaching and learning environments with innovations. Artificial intelligence is a field of science studying and producing machines that think, behave, and solve specific human problems. The study explained the place and role of artificial intelligence chatbots in adult education and the training of adult educators in Nigeria. The article also explored the likely challenges to limiting the successful implementation of artificial intelligence chatbots in adult education. The study concludes with recommendations for policy, practice, and future studies on artificial intelligence chatbots in adult education and the training of adult educators